Tall Tower Ammonia Observations and Emission Estimates in the U.S. Midwest. Issue 11 (16th November 2019) - Griffis, Timothy J.; Hu, Cheng; Baker, John M.; Wood, Jeffrey D.; Millet, Dylan B.; Erickson, Mathew; Yu, Zhongjie; Deventer, M. Julian; Winker, Cody; Chen, Zichong
Abstract: Atmospheric ammonia (NH3 ) has increased dramatically as a consequence of the production of synthetic nitrogen (N) fertilizer and proliferation of intensive livestock systems. It is a chemical of environmental concern as it readily reacts with atmospheric acids to produce fine particulate matter and indirectly contributes to nitrous oxide (N2 O) emissions. Here, we present the first tall tower observations of NH3 within the U.S. Corn Belt for the period April 2017 through December 2018. Hourly average NH3 mixing ratios were measured at 100 and 56 m above the ground surface and fluxes were estimated using a modified gradient approach. The highest NH3 mixing ratios (>30 nmol mol −1 ) occurred during early spring and late fall, coinciding with the timing of fertilizer application within the region and the occurrence of warm air temperatures. Net ecosystem NH3 exchange was greatest in spring and fall with peak emissions of about +50 nmol m −2 s −l . Annual NH3 emissions estimated using state‐of‐the‐art inventories ranged from 0.6 to 1.4 × the mean annual gross tall tower fluxes (+2.1 nmol m −2 s −1 ). If the tall tower observations are representative of the Upper Midwest and broader U.S. Corn Belt regions, the annual gross emissions were +720 Gg NH3 ‐N y −1 and +1, 340 Gg NH3 ‐N y −1, respectively. Finally, considering the N2 O budget over the same region, we estimated total reactive N emissions (i.e., N2 O + NH3 ) of approximately 1, 790 Gg N y −1 from the U.S. Corn Belt, representing 23% of the current annual new N input. Key Points: Observations of NH3 from a tall tower (100 m) provide insights regarding regional emissions from the US Corn Belt Annual NH3 emissions estimated using state‐of‐the‐art inventories were 0.6 to 1.4‐fold compared to the tall tower flux density Annual gross emission estimates for the Upper Midwest and broader US Corn Belt regions were +720 Gg NH3‐N y −1 and +1340 Gg NH3‐N y −1